The Development of Thamma Alphabet Reading and Writing Skill of Students Lao Language and Literature Year 2, Using Cooperative Integrated Reading and Composition or Circ Technique - NANTHAVONG, Vandthong; Thongthavy, Visien; KAMKEINGYOM, Phonesavanh; NANTHAVONG, Phaivone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The objective of this research were to 1) examine the effectiveness of the lesson on the development of reading and writing skills. 2) study the learning effectiveness of students regarding the development of reading and writing skills on Tham alphabet and explore the satisfaction of 2nd year students with the CIRC style of learning at Department of Lao language and Literature, faculty of education, National university of Laos. This research was an experimental research. The population used in the research were 2nd year and 3rd year students of Lao Language-Literature Department, Faculty of Education, National University of Laos 1st semester 2020-2021 academic year in 2 rooms a total of 53 students. The experimental group in the research were 2nd year students with 24 people obtained by specific selection. The research tools were created by the researcher through qualitative research from experts and students which include 1) 3 Lesson plan; 2) Study achievement test form with choose answer 4 options in 1 set has 30 questions, questionnaire about satisfaction in learning with 5 rating scale 12 questions. The statistics used in the analysis were applied intern of percentage, mean and standard deviation. The result revealed that: The effectiveness of the teaching lesson on writing and reading skills of 2nd year students by using the CIRC teaching method has an efficiency of E1/E2 equal to 85.49/89.31 showed that the efficiency is according to the set criteria of 80/80. The effectiveness index of literacy learning about the development of reading and writing skills of 2nd students by using effective CIRC teaching methods (E.I value equal to 0.7307 (showed that students have developed knowledge as a percentage equal to 73.07, and the satisfaction of the students with the management of instruction of Tham alphabet on reading and writing skill of 2nd year students using the CIRC teaching method was at high level with and S.D = 0.64).